Quantitative Voltammetry in Weakly Supported Media. Two Electron Transfer, Chronoamperometry of Electrodeposition and Stripping for Cadmium at Microhemispherical Mercury Electrodes - Limon-Petersen, J; Dickinson, E; Rees, N; Compton, R (2009)
Double potential step chronoamperometry for the two-electron transfer amalgam-forming deposition and stripping of cadmium at a hemispherical mercury electrode in aqueous solution containing different concentrations of supporting electrolyte is compared with simulated results using the Nernst-Planck-Poisson system of equations. The latter were generated using an approximation of zero electric field at the interface [J. Phys. Chem. C 2008, 112, 13716-13728]; the approximation gives a good agreement between theory and experiment, so validating its use for the description of macroelectrode and microelectrode (but not nanoelectrode) problems involving low or negligible levels of supporting electrolyte. © 2009 American Chemical Society.